2018
DOI: 10.1021/acs.joc.8b00633
|View full text |Cite
|
Sign up to set email alerts
|

Mn(OAc)3-Mediated Hydrotrifluoromethylation of Unactivated Alkenes Using CF3SO2Na as the Trifluoromethyl Source

Abstract: A simple and efficient method for hydrotrifluoromethylation of unactivated alkenes was reported. The reaction relied on the single electron oxidation of a commercially available sodium trifluoromethanesulfinate (CFSONa, Langlois' reagent) using Mn(OAc)·2HO as the oxidant and the subsequent addition of trifluoromethyl radical to C═C double bonds. The reaction proceeded readily under mild conditions with good tolerance of a variety of functional groups in the substrates. The preliminary reaction mechanism was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 46 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…On the basis of the results of the control experiments and those of the literature, we proposed a possible mechanism, as illustrated in Scheme . At the beginning, upon UV irradiation, CF 3 SO 2 Na is oxidized to generate ·CF 3 radical under an O 2 -containing atmosphere, and ·CF 3 attacks the amino hydrogen of indole to form nitrogen radical A and CF 3 H . By a 1,3-H shift (detected by 19 F NMR; see the SI), radical A readily isomerizes to carbon radical B .…”
mentioning
confidence: 99%
“…On the basis of the results of the control experiments and those of the literature, we proposed a possible mechanism, as illustrated in Scheme . At the beginning, upon UV irradiation, CF 3 SO 2 Na is oxidized to generate ·CF 3 radical under an O 2 -containing atmosphere, and ·CF 3 attacks the amino hydrogen of indole to form nitrogen radical A and CF 3 H . By a 1,3-H shift (detected by 19 F NMR; see the SI), radical A readily isomerizes to carbon radical B .…”
mentioning
confidence: 99%
“…Recently, we have shown that Mn­(OAc) 3 -mediated hydrotrifluoromethylation of alkenes using CF 3 SO 2 Na as the trifluoromethylating agent and the α-H proton of CH 3 COO – as the H source according to hydrogen abstraction to achieve the last step of hydrogenation process (Scheme ). We anticipated that the hydrogen abstraction process in the final product was driven by the oxidation of CH 3 COOH using Mn­(OAc) 3 ·2H 2 O, and the halotrifluoromethylation reaction may be realized by halogen abstraction if CH 3 COOH was used instead of CF 3 COOH, CCl 3 COOH, or CBr 3 COOH. Due to the stable properties and easy availability of perhalogenated carboxylic acid, it has certain advantages in the synthesis of compounds containing trifluoromethyl (Scheme ).…”
Section: Introductionmentioning
confidence: 88%
“…Previous work on the hydrotrifluoromethylation reaction indicated that the last step of hydrogenation process requires the participation of Mn(OAc) 3 . 22 Calculation results indicated that the energies of C−X bond breaking in CCl 3 COOH and CBr 3 COOH were 61.4 and 45.8 kcal/mol, respectively, which were both lower than that in CH 3 COOH. Therefore, we speculated that CCl 3 COOH and CBr 3 COOH could be used as halogen reagents to achieve the last step of halogenation process on Mn(OAc) 3 -mediated halotrifluoromethylation reactions.…”
Section: ■ Introductionmentioning
confidence: 89%
See 2 more Smart Citations